Mathis der Maler opera in seven tableaux (1938) : a new production by the Theater an der Wien - Hindemith, Paul 1895-1963 (Naxos Rights (Europe) Ltd, 2021)
Set during the turbulence of the German Peasants' revolt in the early stxteenth century, the work's focus is on artistic freedom of expression and human isolation during a time of plague, repression and violence. Hindemith wrote his own libretto finding in Grünewald a metaphor for his own times
Operninszenierung. Österreich. 2012
Wide screen (16:9)
Keywords: Operas; Filmed performances; Opera films; Spectacles filmés; Films d'opéra